Some Issues on Improving the Activity of the Agencies and Units of the National Police of Ukraine - K. L. Buhaichuk (Law and Safety)
The author has studied the main shortcomings of regulatory provision and organization of the activity of the National Police of Ukraine according to certain areas. On the basis of the analysis of the current legislation of Ukraine, by-laws and orders of the Ministry of Internal Affairs of Ukraine and the National Police of Ukraine, the author has formulated propositions aimed at regulating the legal status of the National Police, adoption of basic provisions on its certain types; improvement of the planning procedure within the National Police system, application of modern methods of strategic analysis and goal-setting in its activity; optimization of legal and organizational provision of the activities of police commissions.